2020
DOI: 10.7759/cureus.9792
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin Elevation and Outcome in Subarachnoid Hemorrhage

Abstract: Many cardiopulmonary complications occur after aneurysmal subarachnoid hemorrhage. This is due to sympathetic nervous system activation which results in release of norepinephrine from myocardial sympathetic nerves. Cardiac troponin I is a marker for diagnosis of cardiac injury. Elevated levels of troponin in these patients are associated with worse clinical outcomes. PubMed was searched for literature using regular and Medical Subject Heading (MeSH) keywords for data collection. Papers published in English lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…This can lead to a decrease in the oxygenation index and an increase in lactic acid (LAC) anaerobic metabolism, which in turn can cause an increase in BNP and hs-cTnI levels, it is important to note that these effects are not related to coronary artery disease [19,20]. In this study, it was found that BNP and hs-cTnI levels were signi cantly increased in all patients.…”
Section: Discussionmentioning
confidence: 62%
“…This can lead to a decrease in the oxygenation index and an increase in lactic acid (LAC) anaerobic metabolism, which in turn can cause an increase in BNP and hs-cTnI levels, it is important to note that these effects are not related to coronary artery disease [19,20]. In this study, it was found that BNP and hs-cTnI levels were signi cantly increased in all patients.…”
Section: Discussionmentioning
confidence: 62%
“…Before performing this study, we assumed that there would be a difference in the distribution of the sites of aneurysms. This assumption comes from functional dissection of innervation of the heart 15 and the theory mentioned before that sympathetic nervous system activation causes the change of myocardial biomarkers 16 . Since cortex, subcortical forebrain, brain stem all play roles in the central reflex and sympathetic control of the heart, it's reasonable to find a difference when an aneurysm's rupture affects different parts of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that Tn elevations in stroke are a result of the activation of the sympathoadrenal system and increased catecholamine release, which can lead to direct myocardial toxicity, demand ischemia, LV dysfunction, arrhythmias, possible plaque instability causing MI, and neurogenic sudden cardiac death [ 177 , 186 , 187 , 188 ].…”
Section: Non-cardiovascular Etiologies Of Troponin Elevationmentioning
confidence: 99%